Development of thermostable multiplex qPCR for simultaneous detection of pathogens associated with febrile illnesses - Ali, Mohammad Ridhuan Mohd (2018)
To date, several molecular assays are available for the diagnosis of leptospirosis, melioidosis, invasive salmonellosis and malaria. These reported assays allow early detection of pathogens nucleic acids; hence serve as potential alternatives to the conventional methods including culture, serology and microscopic examination. However, majority of the reported molecular assays lack of internal amplification control (IAC), do not adhere to the MIQE guidelines and usually detect a single organism. To address these major limitations of current molecular assays, this study is aimed to develop a multiplex TaqMan hydrolysis probe-based qPCR that can detect nucleic acids of four different organisms (Leptospira, B. pseudomallei, Salmonella and Plasmodium) and an IAC within a single reaction. To achieve these objectives, four pairs of primers and four TaqMan hydrolysis probes were designed against Leptospira, B. pseudomallei, Salmonella and Plasmodium genomes. These primer pairs were conjugated with a universal adapter (UN-adapter) and combined with UN primers in order to increase the performance of the assay. In addition, another pair of primers and probe against Mycobacterium tuberculosis rpoB gene and Entamoeba histolytica HLY5mc1 gene was also developed as IAC tool. Validation of the assay was performed according to the MIQE guidelines. First, analytical sensitivity of the multiplex qPCR assay was evaluated on 10-fold serial dilutions of genomic DNA from each microbial target, as well as its specificity on 357 microbial isolates, made up of 131 Leptospira isolates, 105 B. pseudomallei isolates, 44 Salmonella isolates, 31 Plasmodium strains and 46 other organisms. Following stability testing at different temperatures, the clinical performance of the qPCR assay was evaluated on 518 retrospective specimens from suspected patients. In this study, it was found that the developed multiplex qPCR assay correctly amplified and differentiated all Leptospira, B. pseudomallei, Salmonella and Plasmodium isolates, with limit of detections (LODs) of 5.61 copies, 8.24 copies, 19.3 copies and 18.1 copies per reaction, respectively. No undesired amplification was observed in other tested organisms. Similarly, the clinical evaluation showed that the qPCR assays had clinical sensitivities of 100% and clinical specificities of between 98.8% and 100%. No evidence of PCR inhibition was observed. In terms of stability, in the presence of 5% trehalose, the lyophilised qPCR mix had an estimated shelf-life of 84.7 days, at ambient temperature. Overall, this study successfully developed a multiplex qPCR assay for early detection of four common febrile causing infections, in particular leptospirosis, melioidosis, invasive salmonellosis and malaria, at high sensitivity and specificity, both analytically and clinically.